Elaboração de uma sequência didática investigativa sobre conservação de energia - SERRA, Lucivaldo Nascimento (2020)
The present work is based on the theoretical proposition of an investigative didactic sequence (SDI) on the benefits of the use of energy conservation. The SDI has as theoretical-methodological references scientific literacy and research teaching. This is of paramount importance for a teaching proposal that aims to encourage teachers to encourage students to use renewable energy. Thus, in order to get them to have access to scientific knowledge, it is necessary a sequential elaboration of language and the epistemology of science by teachers. From this initial information, the proposed didactic sequence has as its crucial point, the way to obtain clean energy through the consciousness of energy conservation, from activities that develop students' scientific skills, such as: the hypothesis test , arguing, working with data, among others. Thus, scientific literacy and research teaching will provide a pedagogical environment that enables the student to broaden his or her worldview and make him / her capable of modifying his / her own reality.